The Effectiveness of Moringa Leaves and Mung Beans on Increasing Hemoglobin Levels of Pregnant Women - Retno Palupi Yonni Siwi,; Kartini Madeira Wati Bachtiar,; Endah Pujiati,; I’im Murtiawani, (Journal of Health Science Community, 2023)
The high rate of anemia in pregnant women is a global problem that must be addressed immediately, because it can have a negative impact on pregnancy, childbirth, the puerperium and disorders of the fetus. The purpose of the study was to analyze the effectiveness of Moringa leaves and green beans on increasing hemoglobin levels of pregnant women. Quasi experimental research design, Two group approach Pre Post Test Design. The population of all pregnant women in the second trimester. Purposive Sampling Technique. Respondents were 22 pregnant women. The independent variables are Moringa leaves and green beans and the dependent variable is the increase in HB levels in pregnant women, the instruments used are SOPs and observation sheets. By identifying and analyzing the effectiveness of Moringa leaves and green beans on increasing hemoglobin levels of pregnant women, it is concluded that there is an effect of Moringa leaves on increasing HB levels in pregnant women. Statistical Test Paired T-test with the results of the significance of X1 Pre and X1 Moringa Leaves Moringa leaves is 0.000<0.05, with a t-count value of -7.420<-2.228 and a significance value of X2 Pre Mung Beans and X2 Post Mung Beans is 0.001<0 ,05, with t value -4.666<-2,228. After being given an intervention for 10 days, it was concluded that Moringa leaves and green beans can increase the Hb level of pregnant women.